Resource scarcity and conflict: An economic analysis - John W. Maxwell; Rafael Reuveny (Fondazione Eni Enrico Mattei (FEEM), 1998)
As time passes, renewable resource scarcities are becoming more common throughout the world. There is increasing evidence that these scarcities are a causal factor in civil unrest and violent conflict, especially in developing countries. We present a simple model of renewable resource dynamics, population dynamics and conflict. Conflict is triggered by per capita resource scarcity. We examine the role and nature of conflict on the bio-economic system. We find that conflict is Nature's way of protecting vital renewable resources from human exploitation. Conflict, as modelled, increases the death rate of the human population, damages the resource, and diverts resources away from harvesting the natural resource. These effects speed the return to a peaceful steady state, at the same time however if conflict results in resource destruction it may destabilise the system leading it towards collapse. On the policy front we find that increasing harvesting efficiency, fertility, and preference for the resource all increase system vulnerability to conflict. Policies directed at raising system carrying capacity, increasing resource growth rate increasing birth control all serve to stabilise the system and reduce its vulnerability to conflict.
Keywords: 330; Konflikt; Ressourcenökonomik; Erneuerbare Ressourcen; Theorie